Analysis of Students' Cognitive Structure through the Assimilation and Accommodation Framework on Work and Energy Material (UNIVERISTAS PGRI MADIUN, 2024)
This study aims to find out how the cognitive structure and problem-solving of high school students in business materials and energy based on the framework of assimilation and accommodation. The method used is a mixed research method with an explanatory sequential design. Data collection was carried out on 53 students in class X using diagnostic test instruments in a five-tier format, then continued with the provision of description tests and interviews to three research subjects with different comprehension categories. The test results showed that students' understanding of concepts was 30.2% in the energy change sub-material, and 52.8% in the non-understanding of concepts in the relationship between potential, kinetic and mechanical energy. Meanwhile, the misconception of the concept was known at 23.6% where students considered the amount of effort to depend on the length of the trajectory taken. Solving problems of subjects with different comprehension categories showed that all three subjects had a less coherent local cognitive structure. Subjects with a conceptual understanding category (S3) have a better assimilation process than subjects with a non-conceptual category (S2). However, it was found that there were subjects with a misconception category (S1) who could solve problems through the assimilation process from beginning to end, this shows that the assimilation process can occur when the subject has the same knowledge scheme as the problem at hand. The accommodation process shows that the subject has a different knowledge scheme with new information/problems faced, especially in mathematical calculations and foreign terms. This is due to associative thinking, intuition and incomplete reasoning.